The Prospects for Increasing the Reuse of Digital Training Content - Shanley, Michael G. (RAND Corporation, 2009)
This study examined how the Advanced Distributed Learning (ADL) Initiative might encourage the reuse of digital training content as a strategy to reduce the cost of its development. While findings highlighted a number of current challenges with the reuse option, one conclusion is that ADL can foster more reuse by taking a proactive approach in supporting training development organizations that are attempting to implement a reuse strategy.